Comprehensive Approach for Evaluating the Potential of the Stavropol Agricultural Territory - Pismennaja, Elena Vjacheslavovna; Loshakov, Alexander Viktorovich; Shevchenko, Dmitrij Aleksandrovich; Odincov, Stanislav Vladimirovich; Kipa, Ljudmila Viktorovna (International Journal of Economics and Financial Issues, 2015)
The provision of food security in Russia under conditions of the WTO and the Customs Union, the food import embargo and sanctions is a complex and multiscale task for supplying industry with the agricultural raw materials and the population with foodstuffs on stable basis and for achieving relative independence from the imports of raw materials and food products. Currently, the agribusiness in the Stavropol Territory is developing faster than the agriculture in the neighboring regions of the North Caucasus Federal District. An analysis of the diversity of natural and socio-economic conditions in this Territory has shown that the existing areas of agricultural specialization do not correspond to the potential of the territory and the food security in general. With the reduction of the state financial support, an increase in the number of unprofitable farms has been marked. The structure of the foodstuff manufacturing (potatoes, fruits, milk, and meat) is increasingly drawn to the small-scale farms. The consequence of the land and economic reforms becomes the imbalance structure of agricultural lands, livestock population, crop acreages and rotations, deterioration of soil fertility indices in large and medium agricultural enterprises. The low yielding natural forage grassland are prevailing. A biologically simplified system of farming has been formed, which leads to a short-term economic effect on the background of the phytosanitary and agrochemical sustainability drop of tillable lands and to the deterioration of the natural environment state. The production and yield of agricultural crops is increasingly dependent on weather conditions. This is unacceptable for the recovery of livestock production and effective arable farming. In accordance with the implementation of the "Strategy of Socio-Economic Development of the North Caucasus Federal District until 2025", the Stavropol Territory in the future will continue focusing on the development of agribusiness. The main tasks of the agricultural production of enterprises should be as follows: the correction of specialization and location of livestock production in view of the natural resource base of the landscape; the increase in the share of green fodders from pastures and hayfields; the use of farming technologies adaptive to the climatic conditions that enhance the productivity of agricultural lands and efficiency of the spent material and technical resources; the conservation of degraded agricultural lands followed by grassing, etc. Such an approach will, on the one hand, prevent the manifestation of the adverse natural processes, and, on the other, ensure the environmental sustainability of the territory and the dynamic development of agribusiness, the economic competitiveness of the Russian market and the possibility of import substitution. Keywords: agriculture, land fund, yield, agricultural lands, agricultural zones. JEL Classifications: F51; Q11; Q13; Q16; Q18; R14